Fetishizing Dialogue and Commodifying Peacemaking (American Journal of Islam and Society, 2009)
This paper assesses the ongoing dialogue and student exchangebetween the Mennonite Central Committee (MCC) and one ofthe most violent institutions in Iran, the Imam Khomeini Educationand Research Institute (IKERI). I will use this relationshipbetween theMCC and IKERI to examine the broader question ofinterreligious transnational dialogue and peacemaking.After a brief background of this somewhat “secretive” dialogue/student exchange, I will evaluate its effects. Of particular interestwill be the following questions: How do we responsibly shapeMuslim–non-Muslim dialogue for peace and understanding in aglobal context that is inevitably shaped by an imbalance of powerand representation? How are the acts of resistance undertaken bythe disenfranchised local/diasporic Iranian communities and thesustained systematic violence against them impacted by a peacefulfaith community such as the Mennonites? How does the absolutizationof “dialogue” coupled with self-proclaimed theologicalmandates effectively strip away the archives of violence from livingmemories and histories?What can examining the decade-longdialogue between the MCC and IKERI reveal about the mechanismsof perpetuation and dissimulation of imperial dominationand control? How can transnational interreligious interventions bethe nexus for infusing sensitivity and expecting accountability?I argue that a fetishization of dialogue and a commodification ofpeacemaking took place between the MCC and IKERI, resultingin the patronage of the sign systems of existing normative ideologiesof violence ...